Cell Wall Proteome Investigation of Bread Wheat (Triticum Aestivum) Developing Grain in Endosperm and Outer Layers. Issue 23 (25th October 2018) - Cherkaoui, Mehdi; Geairon, Audrey; Lollier, Virginie; Clemente, Hélène San; Larré, Colette; Rogniaux, Hélène; Jamet, Elisabeth; Guillon, Fabienne; Francin‐Allami, Mathilde
Abstract: The remodeling of cell wall polysaccharides is controlled by cell wall proteins (CWPs) during the development of wheat grain. This work describes for the first time the cell wall proteomes of the endosperm and outer layers of the wheat developing grain, which have distinct physiological functions and technological uses. Altogether 636 nonredundant predicted CWPs are identified with 337 proteins in the endosperm and 594 proteins in the outer layers, among which 295 proteins are present in both tissues, suggesting both common and tissue specific remodeling activities. These proteins are distributed into eight functional classes. Approximatively a quarter of them were predicted to act on cell wall polysaccharides, with many glycosylhydrolases and also expansin, lyases, and carbohydrate esterases. Therefore, these results provide crucial data to go further in the understanding of relationship between tissue‐specific morphogenesis and cell wall remodeling in cereals. Data are available via ProteomeXchange with identifier PXD010367.